mIR-99a-5p and mIR-148a-3p as candidate molecular biomarkers for the survival of lung cancer patients - Muhammad-Redha Abdullah-Zawawi,; Mira-Farzana Mohamad-Mokhtar,; Saiful Effendi Syafruddin,; Fateen Farhana Ibrahim,; Isa Mohamed Rose,; Roslan Harun,; Nor Azian Abdul Murad, (Penerbit Universiti Kebangsaan Malaysia, 2023)
MicroRNA (miRNA) has emerged as a promising biomarker for improving the current state of an early lung cancer diagnosis. Multiple studies have reported that circulating miRNAs are usually combined in a single panel to determine lung cancer risk. In this study, we sought to assess the prognostic predictive values of the potential miRNAs for lung cancer survival among Malaysian patients. The microarray analysis was performed on the isolated miRNA samples of formalin-fixed lung cancer tissues from Malaysian populations. The correlation between miRNA expression and lung adenocarcinoma (LUAD) patient survival was predicted using TGGA data, followed by extensive in silico analyses, including miRNA target gene identification, protein-protein interaction (PPI) network construction, subnetwork (SN) detection, functional enrichment analysis, gene-disease associations, and survival analysis in advanced-stage LUAD. Overall, two promising miR-99a-5p and miR-148a-3p were upregulated in the patients with good survival. We found that 64 miR-99a-5p and 95 miR-148a-3p target genes were associated with poor prognosis and highly participated in cancer-associated processes, such as apoptosis, mRNA transport and cell-cell adhesion. The density score of 4.667, 3.333, and 3.000 in respective SN1, SN2, and SN3 showed the significant subnetworks of constructed PPI leading to the identification of 17 targets, of which ~79% of them involved in neoplastic diseases. Four high-confidence target genes (SUDS3, TOMM22, KPNA4, and HMGB1) were associated with worse overall survival in LUAD patients, implying their critical roles in LUAD pathogenesis. These findings shed additional light on the roles of miR-99a-5p and miR-148a-3p as potential biomarkers for LUAD survival.